Process evaluation of counseling delivered by a patient navigator in an efficacious smoking cessation intervention among low-income primary care patients - Quintiliani, Lisa M. (Addict Behav Rep, 2019)
INTRODUCTION: This exploratory study examined the relationship between receipt of counseling by a patient navigator and socio-demographic characteristics of primary care patients enrolled in a smoking cessation trial. METHODS: We grouped intervention participants (n = 177) into two categories: 1) no or some contact with the navigator or 2) minimum counseling intervention dose or higher delivered. RESULTS: In logistic regression analyses, controlling for patient race/ethnicity, education, age, gender, household annual income, stress/chaos/hassles composite score, heavy smoking, and substance use, non-Hispanic white participants had lower odds (aOR 0.30; 95% CI 0.13–0.70, p < 0.01) of receiving the minimum intervention dose or higher compared to all other race/ethnicity categories. There was also effect modification such that patients aged 50 or younger who were non-Hispanic white were less likely (aOR 0.09, 95% CI: 0.02-0.54, p < 0.01) to receive the minimum intervention dose compared to older patients from all other race/ethnicity groups. CONCLUSIONS: Future research should explore issues such as acceptability of the intervention to white and younger age participants, and the potential impact of co-occurring substance use disorders on intervention uptake.